Knowledge, attitude and perception regarding HIV/AIDS among postgraduate students of university of Pune - Thakuri, Dipendra Singh; Thapa, Chandra Bahadur (International Journal Of Community Medicine And Public Health, 2018)
Background: HIV/AIDS is still a public health challenge because there is still no cure drug available. Thus, the study was carried out to assess the knowledge, attitude and perceptions regarding HIV/AIDS among postgraduate students of University of Pune. Methods: A cross-sectional study conducted among the students of the University of Pune, Maharashtra, India from July to December 2013. A total of 432 respondents were enrolled in the study. The respondents were selected using simple random sampling and descriptive analysis was done to assess the KAPs. Results: The result shows that all the students had heard about HIV/AIDS. The common source of information was mass media 70.8%. About 79% students had known the cause of HIV/AIDS and 83.4% said correct full form of HIV. However, there were many misconceptions about the routes of transmission. 37% of the students believed that HIV may be transmitted through mosquito’s bite and 16.9% reported that sharing meal with infected people can transmit HIV. A relatively positive attitude towards HIV/AIDS patients was found among students. Nevertheless, about 21% of students avoid care of HIV positive person, 25% rejected to buying food from HIV positive shopkeeper and 21% refused to continue working if worker is HIV positive. Regarding perception, the majority of students had positive perception. Conclusions: All students were aware of HIV/AIDS. Majority of them were aware about route of transmission and prevention. However, the respondents comprising post graduate students, yet there were many misconceptions about route of transmission and significant knowledge, attitude and perception gaps.